2011
DOI: 10.1523/jneurosci.4557-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering Intrinsic Connectional Architecture of Functional Networks in Awake Rat Brain

Abstract: Intrinsic connectional architecture of the brain is a crucial element in understanding the governing principle of brain organization. To date, enormous effort has been focused on addressing this issue in humans by combining resting-state functional magnetic resonance imaging (rsfMRI) with other techniques. However, this research area is significantly underexplored in animals, perhaps due to confounding effects of anesthetic agents used in most animal experiments on functional connectivity. To bridge this gap, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
198
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(225 citation statements)
references
References 42 publications
26
198
0
1
Order By: Relevance
“…Although it has been reported that rats could be trained to undergo fMRI sessions in awake state (Liang et al, 2011), FC studies have been reported as being difficult to apply in mice due to difficulties in acclimating the animals (Jonckers et al, 2013). However, FC pattern in isoflurane anesthetized mice were shown to be strikingly similar to those recorded in the awake state (Jonckers et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been reported that rats could be trained to undergo fMRI sessions in awake state (Liang et al, 2011), FC studies have been reported as being difficult to apply in mice due to difficulties in acclimating the animals (Jonckers et al, 2013). However, FC pattern in isoflurane anesthetized mice were shown to be strikingly similar to those recorded in the awake state (Jonckers et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] Co-registration, based on anatomical images, was performed to a fully segmented rat brain atlas implemented in MIVA for each rat's data set.…”
Section: Mri Data Analysismentioning
confidence: 99%
“…rats [7][8][9] and mice [10]. Moreover since it is shown that both in human [11] and nonhuman primates [12] brain state during rest is not fully comparable with the anesthetized state, new studies increasingly start to study rsfMRI in awake rodents [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%